2019
DOI: 10.1093/tas/txz035
|View full text |Cite
|
Sign up to set email alerts
|

Weaned piglets prefer feed with hydroxychloride trace minerals to feed with sulfate minerals

Abstract: Abstract The aim of this study was to determine whether newly weaned piglets had a preference for diets containing hydroxychloride trace minerals (HTM). To test this, two preference tests were set up. In Exp. 1, the piglets could choose between HTM or inorganic, originating from sulfate trace minerals (STM) in the form of sulfates. Two treatments were applied with high Cu levels (160 ppm Cu added) or low Cu levels (15 ppm Cu added). All diets contained 110 ppm ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…In that study, young calves preferentially consumed creep feed supplements containing concentrated amounts of Cu, Zn, and Mn from hydroxychloride sources vs. sulfate or organic sources. Corroborating our results, previous studies reported weaned pigs also displayed preferential intake of diets formulated with hydroxychloride vs. sulfate sources of Cu, but the preferential response was not as pronounced as the calf studies and decreased with increasing days of exposure to experimental diets ( Van Kuijk et al, 2019 ; Villagomez-Estrada et al, 2020 ). We hypothesized that the response observed in the current study was due to lesser solubility of the hydroxychloride forms of these metals, particularly compared with sulfate and organic alternatives.…”
Section: Resultssupporting
confidence: 85%
“…In that study, young calves preferentially consumed creep feed supplements containing concentrated amounts of Cu, Zn, and Mn from hydroxychloride sources vs. sulfate or organic sources. Corroborating our results, previous studies reported weaned pigs also displayed preferential intake of diets formulated with hydroxychloride vs. sulfate sources of Cu, but the preferential response was not as pronounced as the calf studies and decreased with increasing days of exposure to experimental diets ( Van Kuijk et al, 2019 ; Villagomez-Estrada et al, 2020 ). We hypothesized that the response observed in the current study was due to lesser solubility of the hydroxychloride forms of these metals, particularly compared with sulfate and organic alternatives.…”
Section: Resultssupporting
confidence: 85%
“…Early studies with finishing pigs reported a higher preference for diets supplemented with Cu at 150 mg/kg as hydroxychloride (65% vs. 35%) than diets with Cu sulfate over 15 days [ 8 ]. Likewise, when weaned pigs were offered diets supplemented with Cu at 160 mg/kg as hydroxychloride or sulfate, a strong preference was observed for hydroxychloride compared to sulfate during the first two weeks post-weaning (76% vs. 24% and 81% vs. 19%, respectively) [ 31 ].…”
Section: Discussionmentioning
confidence: 99%